Answer:
x = -4
Explanation:
Simplify the equation. Add common terms together:
5x + 8 - 2 = - 14
5x + (8 - 2) = -14
5x + 6 = -14
Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.
PEMDAS =
Parenthesis
Exponents
Multiplication
Division
Addition
Subtraction
...and is the order of operation in which you follow.
First, subtract 6 from both sides:
5x + 6 (-6) = -14 (-6)
5x = -14 - 6
5x = -20
Next, divide 5 from both sides:
(5x)/5 = (-20)/5
x = -20/5
x = -4
x = -4 is your answer.
~